MENGUKUR PROBABILITAS INDUSTRI BATIK TULIS LASEM BERORIENTASI EKSPOR - Muhammad Tahwin; A. Aviv Mahmudi (STIE Pelita Nusantara Semarang, 2013)
This research aims to prove and explain the influence of corporation, enterprise age, education level, foreign language mastery, number of labours, production capacity and promotion activation to ward export market orientation of batik lasem industry. The tehnigue of data analysis used in this study is logistic regression model. The result of this study shows that the variable of foreingn language mastery influences significantly in predicting export market orientation. While variable of corporation, enterprise age, number of labours, production capacity, promotion activation are not proved to give significant influence in predicting export market orientation. This study is expected to add other factors that are estimated able to predict export market orientation like product quality and capital.